Disability vs the sexual life of women - selected issues - Katarzyna Plagens-Rotman; Grażyna Jarząbek-Bielecka; Piotr Merks; Małgorzata Mizgier; Witold Kędzia; Maciej Wilczak (IMR Press, 2021)
Sex refers to a set of somatic and mental characteristics. The former are determined according to three criteria: gender, external and internal genital organs, and tertiary sex characteristics (breast, specific hair, specific fat distribution, body proportions), the latter distinguish women from men. Every single person experiences problems related to sex - in childhood, adolescence, maturity, old age. In women, these issues are particularly complex at each stage of development. Additionally, during pregnancy, gynaecologists should discuss sexual health with their patients. The sexual health of women with disabilities is a special issue in this respect. Disabilities are a serious social and health problem in both urban and rural agglomerations. Sexual health problems, in the light of these aspects, should also be the task of rural medicine.